Fecundity of the Far-Eastern flatfishes Pleuronectiformes. 1. General characterization of fecundity of Pleuronectiformes in the northern part of the Pacific Ocean - Yury P. Diakov (Известия ТИНРО)
Cited and archive data on fecundity of 31 flatfish species are generalized for the North Pacific. General characterization of the fecundity is presented and correlation between absolute individual fecundity of the females and their body length or age is analyzed and formalized in equation form. Spatial variability of fecundity is described for different species: pacific halibut and starry flounder have the highest absolute fecundity in the eastern Bering Sea and Okhotsk Sea, greenland halibut, yellowfin sole, alaska plaice, sakhalin flounder, longhead dab, and flathead sole - in the Okhotsk Sea, northern rock sole - in the waters at East and West Kamchatka. kamchatka flounder - in the Bering Sea, arrowtooth flounder - in the Pacific waters at North America. So, the Okhotsk Sea is the area where the absolute fecundity of majority wide-spread flatfish species can reach the maximal level. However, the maximal fecundity of longsnouted flounder is higher in the Japan Sea than in the Okhotsk Sea.